The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3847/2041-8213/ad27d4
|View full text |Cite
|
Sign up to set email alerts
|

On the Magnetic Field Properties of Protostellar Envelopes in Orion

Bo 博 Huang 黄,
Josep M. Girart,
Ian W. Stephens
et al.

Abstract: We present 870 μm polarimetric observations toward 61 protostars in the Orion molecular clouds with ∼400 au (1″) resolution using the Atacama Large Millimeter/submillimeter Array. We successfully detect dust polarization and outflow emission in 56 protostars; in 16 of them the polarization is likely produced by self-scattering. Self-scattering signatures are seen in several Class 0 sources, suggesting that grain growth appears to be significant in disks at earlier protostellar phases. For the rest of the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…This is in contrast to the average magnetic field from the POL-2 and ALMA observations, which are approximately perpendicular to the E-W outflow. On the other hand, this is consistent with the Huang et al (2024) survey, where ∼40% of the sources have average magnetic fields perpendicular to the source outflow.…”
Section: Magnetic Fieldssupporting
confidence: 89%
See 1 more Smart Citation
“…This is in contrast to the average magnetic field from the POL-2 and ALMA observations, which are approximately perpendicular to the E-W outflow. On the other hand, this is consistent with the Huang et al (2024) survey, where ∼40% of the sources have average magnetic fields perpendicular to the source outflow.…”
Section: Magnetic Fieldssupporting
confidence: 89%
“…On the other hand, there have been a few surveys of the magnetic field in the inner envelope of protostars comparing the average B-field axis with the outflow axis (Hull et al 2014;Zhang et al 2014;Galametz et al 2018). Most recently, Huang et al (2024) surveyed 61 protostars in Orion (with 56 detections) from the Class 0/I identified disk sources in the VANDAM survey (Tobin et al 2022). They found that ∼40% of the protostars exhibit B-fields that are perpendicular to the source outflows on scales of 400-1000 au, with the remainder of the sources being consistent with random alignment.…”
Section: Introductionmentioning
confidence: 99%